Time to Rethink ‘Orphans and Vulnerable Children’? Findings from a Phenonenological Study in Uganda - Seruwagi, Gloria K. (International Journal of Humanities and Social Science Research, 2015)
The increasing number of ‘orphans and vulnerable children’ (‘OVC’) in sub-Saharan Africa has been the subject of much inquiry and intervention in research, policy and practice. Two major concerns have been highlighted: i) traditional mechanisms for their care and support are overstretched and ii) ‘OVC’ have poor socioeconomic outcomes. Dominant discourses emphasize adults’ central role in ‘OVC’ wellbeing while ‘OVC’ are cast as helpless, passive victims. Study Aim: This research sought to give representation to the voices of ‘OVC’ in constructing their own experiences. Methods: ‘OVC’ were engaged as producers of knowledge and agents of change using innovative child-centred approaches. A total of 129 participants took part in the study including children, caregivers, community members and key informants. Findings: This study found that the majority of existing ‘OVC’ representations are adult constructs not necessarily subscribed to by ‘OVC’. Acknowledging their difficult circumstances, most ‘OVC’ have devised solutions to their challenges and are optimistic despite being constrained by structural and cultural barriers. Traditional care mechanisms have evolved and require strengthening. The lens through which most interventions have been commissioned, implemented and evaluated is paternalistic and does not acknowledge ‘OVC’ competencies. Conclusions: ‘OVC’ voices and lived experiences should inform interventions; also they should be constructed in a more balanced light – showing their challenges while acknowledging their agency in dealing with these challenges.